Optimizing Recovery after Liver Transplantation: Can Functional Therapy-based Re-Education Make a Difference? - Mathew James; Udayakumar Rao (International Journal of Nursing Research, 2025)
Liver transplantation remains the definitive treatment for end-stage liver disease, yet post-operative rehabilitation remains a critical challenge. Despite advancements in surgical techniques and immunosuppressive therapy, transplant recipients frequently experience functional impairments, metabolic complications, and psychosocial distress, significantly impacting long-term recovery. Functional therapy-based re-education (FTBR) has emerged as a multidisciplinary rehabilitation approach designed to optimize post-transplant recovery by integrating physical therapy, occupational therapy, nutritional counseling, and psychological support. Unlike conventional physiotherapy, FTBR employs task-specific training, neuromuscular re-education, and cognitive-motor engagement to enhance physical function, metabolic stability, and mental wellbeing. Evidence suggests that structured FTBR interventions lead to improved muscle strength, mobility, and endurance, reducing the risk of sarcopenia and metabolic syndrome, while also fostering adherence to post-transplant regimens. Moreover, FTBR plays a pivotal role in mitigating cognitive impairments, alleviating psychological distress, and improving quality of life. Studies demonstrate that liver transplant recipients who undergo FTBR experience shorter recovery times, lower hospital readmission rates, and enhanced functional independence. However, barriers such as limited access, program variability, and patient adherence challenges hinder its widespread implementation. Addressing these limitations requires the development of standardized rehabilitation protocols, multidisciplinary collaboration, and increased awareness of FTBR’s benefits. As evidence mounts in favor of structured post-transplant rehabilitation, integrating FTBR into routine liver transplant care may significantly enhance long-term patient outcomes. This review underscores the necessity of adopting a holistic, patient-centered approach to optimize recovery trajectories and ensure sustained health improvements in liver transplant recipients.